Metode Penetapan Harga Jual Produk Sepatu Berdasarkan Cost Plus Pricing Method pada Cv. Tritunggal Sidoarjo - Syaiful Arif; Soenartoto Soenartoto; Darno Darno; Rati Kusumaningtiyas; Siti Nur Afifah; Afiyah Kurniyah (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
The principle of determining the selling price is that the value of the selling price must be higher than the costs incurred because it is added to the desired profit. The use of Cost plus pricing method is based on the selling price principle where the selling price obtained is determined from the total production cost plus the percentage of margin determined by the company. The calculation of order cost is calculated using the variable costing approach. Descriptive Qualitative Method used in this research because the need for data sourced from observations, interviews and documentation to better identify the costs attached to the product. This study concludes that the determination of selling price based on cost plus pricing method is lower than the company calculation. This shows that the selling price based on cost plus pricing method is appropriate to be applied in the CV. Tritunggal Sidoarjo which is engaged in Makloon or Cut, Make, and Trim (CMT) services